Differential expression of the catabolic nahAc gene and its effect on PAH degradation in Pseudomonas strains isolated from contaminated Patagonian coasts - Isaac, Paula (2015)
A combination of RT-PCR assays and of Northern blots were used to evaluate the ability of naphthalene, phenanthrene and pyrene to induce nahAc from three Pseudomonas isolates obtained from oil-contaminated marine sediments. Naphthalene dioxygenase activity based on indigo oxidation correlated with nahAc expression in all strains, while variable polycyclic aromatic hydrocarbon (PAH) degradation behaviors were observed. Naphthalene was completely degraded by all strains; however, whereas high levels of nahAc transcripts were detected in cultures of Pseudomonas monteilii P26 and Pseudomonas stutzeri N3 grown with naphthalene, significantly lower levels were detected in those of Pseudomonas xanthomarina N12. Phenanthrene was degraded by strain P6 and it strongly induced nahAc in this strain. On the other hand, although the strains N12 and N3 removed phenanthrene, the levels of nahAc transcripts were very low when these two strains were grown with this substrate. Remarkably, when P. stutzeri N3 was exposed to pyrene, an intense band of nahAc transcripts was detected by RT-PCR and Northern blot, even though pyrene was degraded to less than 5%. Our results indicate that all the strains from coastal Patagonia displayed the potential to biodegrade PAHs, although in some cases there was no clear correlation between nahAc gene expression and the ability to degrade PAHs.